CRITICAL ANALYSIS IN THE ROLE OF BIOMEDICAL EQUIPMENT TECHNICIANS IN HEALTHCARE FACILITIES. - HadiMohammed BakhtanAlwaeli, Ali Hamad Mohammed Al mansour, Abdullah Awadh Ali Al Mubti, Abdullah Hamad Mohammed Alajabi, Hamad Ali Mohammed Alajabi, Tareg Hamad MaslahAlwaieli, Fayez Theeb Saleh Alyami (Chelonian Research Foundation, 2023)
Biomedical equipment technicians (BMETs) play a vital part in overseeing the operation and safety of therapeutic hardware in restorative offices. This article analyzes their parts, challenges, and needs in guaranteeing patient safety and quality care. Through a comprehensive literature review and examination of strategies utilized in BMETs, this study highlights their significance in giving restorative care. BMET makes a difference in securing quiet well-being by carefully assessing and repairing beneficial hardware and diminishing the dangers related to equipment disappointment. Despite their imperative part, BMETs still confront progressing and current challenges that require proficient advancement, such as the quick progression of innovation, constrained capacity, and changing administrative necessities. Also, this examination highlights the need to encourage the coordination of BMET into the healthcare framework, joining hands with other doctors to progress its adequacy and increment participation. Keywords: Biomedical Equipment Technicians, healthcare facilities, maintenance, patient safety, equipment management